The public’s perception of the Territorial Defence Forces in Poland - Zielińska, Małgorzata (Sodobni vojaški izzivi, 2021)
The functioning and activities of the Territorial Defence Forces and the behaviour of its soldiers are among the many interests of the Military Office of Social Research in the Military Centre for Civic Education, which conducts social research in the military environment. Poles were asked if they believed that the tasks of this new formation should primarily be assistance in actions to combat the effects of natural and other disasters, defence of local people and infrastructure, or other military operations. The Territorial Defence Forces engaged in the fight against the consequences of the pandemic in Poland. The main goal of this article is to present the major Polish research dedicated to the Polish Territorial Defence Forces.
Keywords: crisis management; družbena percepcija; družbene raziskave; krizno upravljanje; Poljska; SARS-CoV 2; social perception; social research; Teritorialna obramba; Territorial Defence Forces